2013
DOI: 10.1158/1541-7786.mcr-12-0544
|View full text |Cite
|
Sign up to set email alerts
|

CDCP1 Regulates the Function of MT1-MMP and Invadopodia-Mediated Invasion of Cancer Cells

Abstract: Complement C1r/C1s, Uegf, Bmp1 (CUB) domain-containing protein 1 (CDCP1) is a transmembrane protein that regulates anchorage-independent growth and cancer cell migration and invasion. Expression of CDCP1 is detected in a number of cancer cell lines and tissues and is closely correlated with poor prognosis. Invadopodia are actin-based protrusions on the surface of invasive cancer cells that promote the degradation of the extracellular matrix (ECM) via localized proteolysis, which is mainly mediated by membrane … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 43 publications
1
38
0
1
Order By: Relevance
“…5C and D). Recently, we reported that CDCP1 may be involved in a lipid raftdependent secretary pathway (43). It is reasonable to speculate that CDCP1 also plays a role in Ras-induced cell motility and invasion by regulating focal adhesion and MMP2 activation and MMP9 secretion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5C and D). Recently, we reported that CDCP1 may be involved in a lipid raftdependent secretary pathway (43). It is reasonable to speculate that CDCP1 also plays a role in Ras-induced cell motility and invasion by regulating focal adhesion and MMP2 activation and MMP9 secretion.…”
Section: Discussionmentioning
confidence: 96%
“…It is reasonable to speculate that CDCP1 also plays a role in Ras-induced cell motility and invasion by regulating focal adhesion and MMP2 activation and MMP9 secretion. Moreover, CDCP1 is associated with MT1-MMP, which is an activator of both MMP2 and MMP9 (43). It is speculated that CDCP1 can regulate activation of MMP2 and MMP9 through membrane trafficking of MT1-MMP to the same intracellular compartment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LDs appear to be not merely inert structures for lipid storage, but dynamic signaling organelles (58,59). The literature supports the cross-talk between cellular LDs and membrane lipid rafts (60)(61)(62), where multiple proteins involved in migration, including integrins (63,64) and CDCP1 (54,65), reside. On the other hand, the biophysical properties of high-lipid vs. lowlipid cells remain unknown and await investigation.…”
Section: Low-lipid Content Favors Promigratory Phenotype Of Breast Camentioning
confidence: 89%
“…Anoikis is a form of cell death triggered by loss of interaction with the extracellular matrix [47]. In studies conducted by Miyazawa et al [48], autophagy was shown to be involved in anoikis of lung cancer cells caused by suppression of CDCP1. Cell death induced by knocking down CPCD1 in A549 (NSCLC) cells under suspension conditions was caspase 3 (a marker for apoptosis) independent.…”
Section: Autophagic Cell Death In Lung Cancer Cellsmentioning
confidence: 99%